The Memory Effect : The Remediation of Memory in Literature and Film - Ty, Eleanor Rose, 1958-; Kilbourn, Russell J. A. (Russell James Angus), 1964- (Book collections on Project MUSE., 2013)
The Memory Effect is a collection of essays on the status of memory--individual and collective, cultural and transcultural--in contemporary literature, film, and other visual media. Contributors look at memory's representation, adaptation, translation, and appropriation, as well as its mediation and remediation. Memory's irreducibly constructed nature is explored, even as its status is reaffirmed as the basis of both individual and collective identity. The book begins with an overview of the field, with an emphasis on the question of subjectivity. In separate sections, contributors examine literature and its relation to cultural memory; autobiography and life writing, especially those lives shaped by trauma and forgotten by history; cinema and its intimate and mutually constitutive relationship with memory and history; and individual and collective memory in the context of contemporary visual texts, at the crossroads of popular and avant-garde cultures. Russell J. A. Kilbourn is an associate professor in the Department of English and Film Studies at Wilfrid Laurier University. He is the author of Cinema, Memory, Modernity: The Representation of Memory from the Art Film to Transnational Cinema (2010). Eleanor Ty is a professor of English at Wilfrid Laurier University. Publisher's note.